Socially responsible investment practices and implementation approaches: a case study of listed extractive firms in Ghana - Cudjoe, Mawuena Akosua; Abdul Latiff, Ahmed Razman; Abu Kasim, Nor Aziah; Osman, Mohammad Noor Hisham (Informa UK Limited, 2023)
We explore the socially responsible investment practices and implementation approaches of some extractive listed firms through the lens of institutional theory. Using an interpretive case study approach with data collected from interviews, observations, and archival documents, over 10 months, we find that the SRI practices of the firms were in line with the SDGs. Furthermore, we reveal that the case firms’ choice of practices along the SDGs was because of the government’s drive for SRI practices in line with the SDGs. We also observe that the government-dominated case firm used its SRI practices to augment the developmental activities of the government. Finally, we show that alien to literature, a multinational company implements its SRI practices using the global approach, because of the pressure from its parent company. Our empirical findings possess the rigour expected from qualitative research. The empirical findings are credible, dependable, and confirmable. In ensuring credibility, the interviews were recorded. However, detailed notes were taken of the interviewees who refused to be recorded. The transcribed data were resent to the interviewees to ensure what they said was accurately captured. Recruiting qualified assistants to undertake some interviews, providing in-depth descriptions of the research method and the analysis of the findings from both the intra and cross-case perspective ensured that the findings are dependable. Finally, the use of semi-structured interviews where further clarity was sought when needed makes the empirical findings confirmable. Largely, our findings support the institutional theory, albeit with some deviations.